2004
DOI: 10.1111/j.1075-122x.2004.21392.x
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz-Associated Gynecomastia: Report of Five Cases and Review of the Literature

Abstract: The prognosis of HIV infection has improved dramatically since the introduction of highly active antiretroviral therapy (HAART). However, numerous adverse effects and limitations regarding tolerability remain a concern. Lipomastia (pseudogynecomastia), a breast enlargement due to central adiposity, may occur as part of a fat redistribution syndrome which has been associated with HAART regimens and several pathogenic mechanisms have been advocated in its development. Here we report an observational longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 11 publications
6
28
0
Order By: Relevance
“…In contrast, previous case series do not report any cases of gynaecomastia in adolescents [6, 7, 12, 15, 1719]. Cross-sectional data from the general population has shown that gynaecomastia occurs in 4% of adolescent boys aged 10–19 years [20].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, previous case series do not report any cases of gynaecomastia in adolescents [6, 7, 12, 15, 1719]. Cross-sectional data from the general population has shown that gynaecomastia occurs in 4% of adolescent boys aged 10–19 years [20].…”
Section: Discussionmentioning
confidence: 90%
“…The proposed mechanism from in vitro data is that efavirenz mimics the effects of oestrogen on breast tissue [14]. Two other hypothesized mechanisms have been suggested for ART-associated gynaecomastia: immune restoration may increase breast tissue oestrogen availability, and efavirenz has been shown to increase the area under the curve of ethinyl oestradiol by at least 37%, thereby elevating the oestrogen–androgen ratio [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Upon a change of regimen, resolution was seen in all cases after several months. 9 In vitro experiments have suggested that efavirenz activates oestrogen receptors in breast tissue, 10 although subsequent experiments to confirm this finding have not yet been conducted. A systematic review concluded that the quality of the evidence of the association between gynaecomastia and antiretroviral drugs was moderate in general, being most convincing with efavirenz.…”
Section: Discussionmentioning
confidence: 99%
“…Large prospective studies have documented an association between gynaecomastia and EFV and didanosine. 10 EFV is known to induce gynaecomastia by direct oestrogen receptor modulation, 2 an effect that varies with ethnicity and weight. 11 Mutations in CYP2B6 have been reported throughout Africa, 12 as well as in Germany, 13 resulting in impaired hepatic metabolism of EFV.…”
Section: Respiratorymentioning
confidence: 99%